Modern Electroencephalographic Assessment Techniques Theory and Applications - Sakkalis, Vangelis; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
Modern Electroencephalographic Assessment Techniques: Theory and Applications presents numerous signal processing and connectivity analysis methodologies addressing a wide variety of clinical applications including epilepsy, schizophrenia, Alzheimer’s disease, and even alcoholism. Among the different topics addressed, the neurophysiological basis of cognitive processes is also investigated. The goal is to provide a comprehensive overview of the most modern and widely established approaches mainly applied in, but not limited to, decomposing high resolution multichannel Electroencephalography (EEG) and Magnetoencephalography (MEG) signals into functional interconnected brain regions. Synergistic approaches linking both EEG/ MEG and functional Magnetic Resonance Imaging (fMRI) techniques are also discussed. In line with the popular Neuromethods series, chapters present the theoretical basis of each method along with prosperous application domains, in the form of a balanced mixture of theoretical tutorials, comprehensive reviews, and original research. Emphasis is given to the underlying assumptions, to technical matters that greatly affect the outcome of each proposed method, to the ambitions, and to the domain of application of each method. Furthermore, links to graph theory and visualization of connectivity motifs is also addressed in an attempt to better describe the functional characteristics of brain networks.   Authoritative and practical, Modern Electroencephalographic Assessment Techniques: Theory and Applications touches upon both the biomedical and computational aspects of this exciting and rapidly evolving field, and will allow for a more in-depth, vital understanding of the brain’s complex underlying mechanisms.
Operational Architectonics Methodology for EEG Analysis: Theory and Results -- Clinical Electroencephalography in the Diagnosis and Management of Epilepsy -- Effective Brain Connectivity from Intracranial EEG recordings: Identification of Epileptogenic Zone in Human Focal Epilepsies -- On the Effect of Volume Conduction on Graph Theoretic Measures of Brain Networks in Epilepsy -- Methods for Seizure Detection and Prediction: An Overview -- Graph-Theoretic Indices of Evaluating Brain Network Synchronization: Application in an Alcoholism Paradigm -- Time-Varying Effective Connectivity for Investigating the Neurophysiological Basis of Cognitive Processes -- Assessment of Sensory Gating Deficit in Schizophrenia Using a Wavelet Transform Methodology on Auditory Paired-Click Evoked Potentials -- Schizophrenia Assessment Using Single Trial Analysis of Brain Activity -- Phase Variants of the Common Spatial Patterns Method -- Estimation of Regional Activation Maps and Interdependencies from Minimum Norm Estimates of Magnetoencephalography (MEG) Data -- Blind Signal Separation Methods in Computational Neuroscience -- Current Trends in ERP Analysis Using EEG and EEG/ fMRI Synergistic Methods -- Computer-Based Assessment of Alzheimer’s Disease Employing fMRI and/or EEG: A Comprehensive Review.
Keywords: Neurosciences; Neurology .; Neurosciences; Neurology